Inhibiting MiR-320a promotes myocardial apoptosis in myocardial infarction rats through activating VEGF pathway: MiR-320a in myocardial infarction rats - Liu, Yong; Wang, Ting; Lai, Hongmei; Shen, Jingyi; Gao, Fangming (Cellular and Molecular Biology, 2023)
To detect the expressions of vascular endothelial growth factor (VEGF) and micro ribonucleic acid (miR)-320a in myocardial cells of rats with myocardial infarction (MI), and to study the detailed mechanism of the role of miR-320a in myocardial apoptosis in MI rats. The Sprague-Dawley rat model of MI was established, and the rats were randomly divided into a control group (n=8), recombinant adeno-associated virus (rAAV)-miR-320a group (n=8) and rAAV-miR-320a TuDs group (n=8). The corresponding rAAV (1×1011 virion-like particles) was intravenously injected. At 2 weeks after the injection of rAAV, all rats were euthanatized, and the organs were collected, frozen in liquid nitrogen and stored at -80°C for further experiments. The total RNA and total protein were extracted from heart tissues, and the expression levels of rAAV-miR-320a and rAAV-miR-320aTuDs in heart tissues were determined via reverse transcription-polymerase chain reaction (RT-PCR). Moreover, RT-PCR and Western blotting were performed to detect the mRNA and protein expressions in heart tissues, respectively. At the same time, myocardial apoptosis was evaluated through flow cytometry. After treatment with miR-320a TuDs, the mRNA and protein expressions of VEGF in heart tissues in MI were significantly increased (P<0.05). The results of flow cytometry showed that miR-320a TuDs intervention could promote myocardial apoptosis in MI (P<0.05). In addition, the results of Western blotting revealed that miR-320a TuDs could facilitate the activation of the VEGF signaling pathway in heart tissues in MI (P<0.05). Inhibiting miR-320a can promote myocardial apoptosis through activating the VEGF signaling pathway in myocardial cells in MI.